ANALISIS KOMPARASI KINERJA KEUANGAN PT GOTO GOJEK TOKOPEDIA TBK DAN GRAB HOLDINGS LTD BERDASARKAN RASIO KEUANGAN - Arjuna Sam, Rifki; Rayyani, Wa Ode; Fauda, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and compare the financial performance of PT GoTo Gojek Tokopedia Tbk and Grab Holdings Ltd during the 2022–2024 period using financial ratio analysis. This research employed a quantitative descriptive method using secondary data obtained from the annual financial statements of both companies. The financial ratios used include liquidity ratios (Current Ratio, Quick Ratio, Cash Ratio), solvency ratios (Debt to Equity Ratio, Debt to Asset Ratio), activity ratios (Total Asset Turnover, Fixed Asset Turnover), and profitability ratios (Net Profit Margin, Return on Assets, Return on Equity, Return on Investment). Data analysis was conducted by comparing the ratio results with industry standards according to Kasmir (2019). The results indicate that in terms of liquidity ratios, both companies are categorized as having good financial performance because their Current Ratio, Quick Ratio, and Cash Ratio values are above the industry standard. In terms of solvency ratios, both companies are also categorized as good because their Debt to Equity Ratio and Debt to Asset Ratio values are below the industry standard. However, in terms of activity and profitability ratios, both companies are still categorized as unfavorable because their ratio values remain below industry standards. Nevertheless, Grab Holdings Ltd demonstrated relatively better performance in liquidity, activity, and profitability aspects compared to PT GoTo Gojek Tokopedia Tbk during the research period, while PT GoTo Gojek Tokopedia Tbk showed stronger solvency and cash position.